Value of bronchogram sign on CT images in differentiating benign and malignant solid pulmonary nodules with maximum diameter ≤2 cm - ZHANG Chun; LI Qi; LYU Fajin; HUO Jiwen; HE Xiaoqun (陆军军医大学学报, 2022)
Objective To investigate the relationship between solid pulmonary nodules with maximum diameter≤2 cm and the bronchi in order to provide more valuable clues to differentiate benign and malignant solid pulmonary nodules. Methods The clinical and CT data of 776 patients with solid pulmonary nodule at a maximum diameter of not larger than 2 cm confirmed by pathology in our hospital from January 2014 to January 2021 were analyzed retrospectively. According to pathological types, the patients were divided into malignant nodule group(n=340) and benign nodule group(n=436), and those with benign nodules were further assigned into inflammatory nodule subgroup(n=299) and benign tumor subgroup(n=137). Bronchogram sign on CT images were classified into 4 types according to the relationship between pulmonary nodules and bronchi. The incidence and types of different bronchogram sign on CT images were compared between malignant nodule group and benign nodule group, and between inflammatory nodule subgroup and benign tumor subgroup. The diagnostic performance of bronchogram sign on CT images to differentiate benign and malignant solid pulmonary nodules was evaluated. Results ① The incidence of bronchogram sign on CT images was higher in the malignant nodule group than the benign nodule group(65.9% vs 31.4%, P < 0.001). Types Ⅰ and Ⅱ signs were more common in the benign nodule group, while Types Ⅲ and Ⅳ signs were more common in the malignant nodule group(all P < 0.01). The sensitivity, specificity, and accuracy of bronchogram sign on CT images was 82.1%, 56.2%, and 72.3%, respectively in differentiation of benign and malignant solid pulmonary nodules. ②The incidence of bronchogram sign on CT images was statistically higher in the inflammatory nodule subgroup than the benign tumor subgroup(39.1% vs 14.6%, P < 0.001). Type Ⅳ was more common in inflammatory nodule subgroup(P < 0.05). However, no significant differences were observed in the other 3 types between the 2 subgroups (all P > 0.05). Conclusion Bronchogram sign on CT images is valuable in differentiation of benign and malignant solid pulmonary nodules measuring ≤2 cm in diameter. Irregular air bronchogram sign or truncation of bronchus in the margin of nodule is highly suggestive of malignancy.